Specificity of understanding love collisions "from the modern life" in M. Kuzmin’s little prose - Полякова, Евгения Олеговна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article offers the analysis of the poetics of M. Kuzmin’s novels – "The decision of Anna Meyer" (1907) and "Platonic Charlotte" (1914), in which the author adverts to the issue of love. Both short stories reveal similarities characteristic of writer’s unstylized little prose. M. Kuzmin’s irony is most clearly manifested in these works. It has been shown on the plot-compositional level of short stories: in relationships between the characters and in the balance of short-story pointes, creating a comic effect. Intertext and the playing with the reader plays an important role in short stories.